2016
DOI: 10.1111/jcpt.12404
|View full text |Cite
|
Sign up to set email alerts
|

Will peripherally restricted kappa-opioid receptor agonists (pKORAs) relieve pain with less opioid adverse effects and abuse potential?

Abstract: Summary What is known and objective Optimal utilization of opioid analgesics is significantly limited by the central nervous system adverse effects and misuse/abuse potential of currently available drugs. It has been postulated that opioid‐associated adverse effects and abuse potential would be greatly reduced if opioids could be excluded from reaching the brain. We review the basic science and clinical evidence of one such approach – peripherally restricted kappa‐opioid receptor (KOR) agonists (pKORAs). Metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
99
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(104 citation statements)
references
References 91 publications
(121 reference statements)
2
99
0
Order By: Relevance
“…The μ receptor agonists are efficacious analgesics (Spetea et al, 2013b;Pasternak, 2014) but induce unwanted euphoria, addiction, respiratory depression and gastrointestinal tract inhibition (Benyamin et al, 2008;Atkinson et al, 2014). The κ receptor modulates pain processing at central and peripheral sites, and pain remains a likely indication for κ agonists (Kivell and Prisinzano, 2010;Albert-Vartanian et al, 2016). Moreover, κ agonists do not cause the liabilities of μ receptor activation.…”
Section: Introductionmentioning
confidence: 99%
“…The μ receptor agonists are efficacious analgesics (Spetea et al, 2013b;Pasternak, 2014) but induce unwanted euphoria, addiction, respiratory depression and gastrointestinal tract inhibition (Benyamin et al, 2008;Atkinson et al, 2014). The κ receptor modulates pain processing at central and peripheral sites, and pain remains a likely indication for κ agonists (Kivell and Prisinzano, 2010;Albert-Vartanian et al, 2016). Moreover, κ agonists do not cause the liabilities of μ receptor activation.…”
Section: Introductionmentioning
confidence: 99%
“…Difelikefalin (CR845) is a peripherally restricted and selective agonist at KORs, with no identified off-target activity. 18 Its unique all D-amino acidÀbased peptide structure is different from small organic heterocycle KOR agonists studied to date, which activate both central and peripheral KORs in addition to other receptors. Preclinical studies demonstrated that due to its physicochemical properties, difelikefalin does not penetrate the blood-brain barrier and thus may not produce the undesirable central nervous system effects related to activation of central KORs (e.g., dysphoria, hallucinations).…”
mentioning
confidence: 99%
“…Likewise, the mechanisms of opioid sparing remain to be elucidated, but are at least partially mediated by overall analgesic requirements, given the self‐tapering nature of patients' opioid dosing after the initiation of cannabis therapy (Boehnke et al, ; Haroutounian et al, ). Peripherally restricted opioid agonists are also undergoing intense investigation, because of their inability to produce the adverse effects mediated by the central nervous system (Albert‐Vartanian et al, ). Although this approach has great potential utility in clinical practice, to date, there is only one peripherally restricted opioid undergoing Phase II clinical trials (κ receptor agonist JNJ‐38488502; Olesen et al, ).…”
Section: The Future Of Opioid Therapymentioning
confidence: 99%